2015
DOI: 10.1111/cdev.12367
|View full text |Cite
|
Sign up to set email alerts
|

Infant Temperament: Stability by Age, Gender, Birth Order, Term Status, and Socioeconomic Status

Abstract: Two complementary studies focused on stability of infant temperament across the first year and considered infant age, gender, birth order, term status, and socioeconomic status (SES) as moderators. Study 1 consisted of 73 mothers of firstborn term girls and boys queried at 2, 5, and 13 months of age. Study 2 consisted of 335 mothers of infants of different gender, birth order, term status, and SES queried at 6 and 12 months. Consistent positive and negative affectivity factors emerged at all time-points across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
70
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 164 publications
(181 reference statements)
9
70
0
5
Order By: Relevance
“…These results are consistent with the generally similar stability of temperament in girls and boys (with some exceptions: Bornstein et al, 2015; Garcia Coll et al, 1992), in the only studies (to our knowledge), examining child sex as a moderator. However, any discrepancy, or instance of disagreement with respect to differences between girls’ and boys’ temperament stability, could represent a cultural difference, wherein South Korean female and male infants demonstrate stability across different attributes than their U.S. counterparts.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…These results are consistent with the generally similar stability of temperament in girls and boys (with some exceptions: Bornstein et al, 2015; Garcia Coll et al, 1992), in the only studies (to our knowledge), examining child sex as a moderator. However, any discrepancy, or instance of disagreement with respect to differences between girls’ and boys’ temperament stability, could represent a cultural difference, wherein South Korean female and male infants demonstrate stability across different attributes than their U.S. counterparts.…”
supporting
confidence: 91%
“…Parental treatment of first- and laterborns is often not consistent, and siblings’ different experiences (their nonshared environments) in growing-up contribute to making them distinctive individuals (Plomin & Daniels, 1987; Stoolmiller, 1999; Turkheimer & Waldron, 2000). Nonetheless, Bornstein et al (2015) reported no differences in stability of temperament in first- vs. secondborns over the first year of life.…”
mentioning
confidence: 89%
See 3 more Smart Citations